Watershed : a novel - Barr, Mark (Hub City Press, 2019)
Amidst construction of a federal dam in rural Tennessee, Nathan, an engineer hiding from his past, meets Claire, a small-town housewife struggling to find her footing in the newly-electrified, job-hungry, post-Depression South. As Nathan wrestles with the burdens of a secret guilt and tangled love, Claire struggles to balance motherhood and a newfound freedom that awakens ambitions and a sexuality she hadn't known she possessed. The arrival of electricity in the rural community, where prostitution and dog-fighting are commonplace, thrusts together modern and backcountry values. In an evocative feat of storytelling in the vein of Kent Haruf's Plainsong, and Ron Rash's Serena, Watershed delivers a gripping story of characters whose ambitions and yearnings threaten to overflow the banks of their time and place. As the townspeople embark on a biblical undertaking to harness elemental forces, Nathan and Claire are left to wonder what their lives will look like when the lights come on.